Ethics-based AI auditing core drivers and dimensions: A systematic literature review - Laine, Joakim (My University, 2021)
This thesis provides a systematic literature review (SLR) of ethics-based AI auditing research. The review’s main goals are to report the current status of AI auditing academic literature and provide findings addressing the review objectives. The review incorporated 50 articles presenting ethics-based AI auditing. The SLR findings indicate that the AI auditing field is still new and rising. Most of the studies were conference proceeding published either 2019 or 2020. Therefore, there was a demand for a SLR work as the AI auditing field was wide and unorganized. Based on the SLR findings, fairness, transparency, non-maleficence and responsibility are the most important principles for the ethics-based AI auditing. Other commonly identified principles were privacy, beneficence, freedom and autonomy and trust. These principles were interpreted to belong to either drivers or dimensions depending on whether something is audited directly or whether achieving ethics is a desired outcome. The findings also suggest that the external AI auditing leads the ethics-based AI auditing discussion. Majority of the papers dealt specifically with external AI auditing. The most important stakeholders were recognized to be researchers, developers and deployers, regulators, auditors, users and individuals and companies. Roles of the stakeholders varied depending on whether they are proposed to conduct AI audits or whether they are in the position of beneficiary.

Tässä Pro gradu -tutkielmassa esitellään systemaattinen kirjallisuuskatsaus etiikkalähtöiseen tekoälyn auditointiin. Kirjallisuuskatsauksen keskeisimmät tavoitteet ovat esittää tämänhetkinen tila tekoälyn auditoinnin akateemisesta kirjallisuudesta sekä esittää keskeisimmät löydökset tutkielman tavoitteiden mukaisesti. Kirjallisuuskatsaus sisälsi 50 artikkelia, mitkä käsittelivat etiikkalähtöistä tekoälyn auditointia. Systemaattisen kirjallisuuskatsauksen löydökset osoittivat, että tekoälyn auditoinnin ala on edelleen uusi ja kasvava. Suurin osa julkaisuista oli konferenssipapereita vuosilta 2019-2020. Ala on myös laaja sekä epäorganisoitu, joten systemaattiselle kirjallisuuskatsaukselle oli kysyntää. Löydöksien perusteella reiluus, läpinäkyvyys, ei-haitallisuus sekä vastuullisuus ovat tärkeimmät periaatteet etiikkalähtöiseen tekoälyn auditointiin. Muut yleisesti tunnistetut periaatteet olivat yksityisyys, hyvyys, vapaus ja autonomia sekä luottamus. Nämä periaatteet tulkittiin kuuluvaksi joko ajureihin tai dimensioihin sen perusteella auditoitiinko periaatetta suoraan vai oliko periaatteen saavuttaminen auditoinnin toivottu tulos. Löydökset osoittivat myös, että ulkoinen auditointi hallitsee tämänhetkistä keskustelua etiikkalähtöisessä tekoälyn auditoinnissa. Valtaosa papereista käsitteli erityisesti ulkoista tekoälyn auditointia. Lisäksi tärkeimmät sidosryhmät tunnistettiin. Nämä olivat tutkijat, järjestelmän kehittäjät, lainvalvojat, auditoijat, käyttäjät sekä yksilöt ja organisaatiot. Heidän roolinsa vaihtelivat sen perusteella vastasivatko he tekoälyn auditoinnin toteuttamisesta vai kuuluivatko he tekoälyn auditoinnin edunsaajiin.
Keywords: artificial intelligence, AI, auditing, ethics, machine learning, principles, systematic review, SLR